High parathyroid hormone predicts exacerbations in COPD patients with hypovitaminosis D. (June 2021) - Amado, Carlos A.; Muñoz, Pedro; García-Unzueta, Mayte; Agüero, Juan; Tello, Sandra; Fueyo, Paula; Vega, Carmen; Lavín, Bernardo A.; Guerra, Raúl A.; Casanova, Ciro
Abstract: Background: Hypovitaminosis D has been linked to deterioration in clinical parameters and lung function in COPD. As a response to low levels of vitamin D serum Parathyroid Hormone (iPTH) is increased in some, but not all, patients. The aim of this study was to determine whether COPD patients with elevated PTH levels are at higher risk of COPD exacerbations and hospitalizations. Methods: 166 COPD outpatients were randomly preselected. Clinical and analytical characteristics were assessed at baseline. After excluding patients with other conditions known to disturb calcium metabolism 141 patients were identified. Except one, all patients were prospectively followed for 12 months after obtaining the blood samples. Hypovitaminosis D was considered when serum 25(OH)D < 30 ng/mL. Secondary hyperparathyroidism was considered when serum iPTH was higher than normal (50 pg/mL) in patients with hypovitaminosis D. COPD exacerbations and hospital admissions were recorded during the follow-up. Results: Prevalence of hypovitaminosis D in COPD patients was 89.3%, prevalence of secondary hyperparathyroidism associated with hypovitaminosis D was 22, 9%. Cox proportional risk analysis showed that patients belonging to the high iPTH-low 25(OH)D group were at a higher risk of moderate COPD exacerbations (HR 1.81 (CI95% 1.043–3.127), p = 0.035) and hospital admissions (HR 5.45 (CI95% 2.018–14.720), p = 0.002) as compared with those with normal iPTH-low 25(OH)D levels. Conclusions: COPD patients with hypovitaminosis D and elevated iPTH have higher risk of moderate exacerbations and hospitalizations than those with hypovitaminosis D and normal iPTH. Highlights: Hypovitaminosis D has been associated with COPD exacerbations and other clinical parameters. iPTH is increased in some patients with low levels of vitamin D. iPTH correlates negatively with important outcomes in COPD such as FEV1 or 6 min walking distance. COPD patients with hypovitaminosis D and elevated iPTH have higher risk of moderate exacerbations and hospitalizations.